Modes of Micromolar Host-Guest Binding of β-Cyclodextrin Complexes Revealed by NMR Spectroscopy in Salt Water - Tomeček, Josef; Čablová, Andrea; Hromádková, Aneta; Novotný, Jan; Marek, Radek; Durník, Ivo; Kulhánek, Petr; Prucková, Zdeňka; Rouchal, Michal; Dastychová, Lenka; Vícha, Robert (The Journal of organic chemistry, 2021)
Multitopic supramolecular guests with finely tuned affinities toward widely explored cucurbit[n]urils (CBs) and cyclodextrins (CDs) have been recently designed and tested as functional components of advanced supramolecular systems. We employed various spacers between the adamantane cage and a cationic moiety as a tool for tuning the binding strength toward CB7 to prepare a set of model guests with KCB7 and Kβ-CD values of (0.6-5.0) × 1010 M-1 and (0.6-2.6) × 106 M-1, respectively. These accessible adamantylphenyl-based binding motifs open a way toward supramolecular components with an outstanding affinity toward β-cyclodextrin. 1H NMR experiments performed in 30% CaCl2/D2O at 273 K along with molecular dynamics simulations allowed us to identify two arrangements of the guest@β-CD complexes. The approach, joining experimental and theoretical methods, provided a better understanding of the structure of cyclodextrin complexes and related molecular recognition, which is highly important for the rational design of drug delivery systems, molecular sensors and switches.
Keywords: beta-cyklodextriny; Molecular Structure; voda; cyklodextriny; molekulární struktura; magnetická rezonanční spektroskopie; Water; Magnetic Resonance Spectroscopy; beta-Cyclodextrins; Cyclodextrins